Premature ovarian insufficiency: a toolkit for the primary care physician. (3rd September 2021) - Lambrinoudaki, I.; Paschou, S. A.; Lumsden, M. A.; Faubion, S.; Makrakis, E.; Kalantaridou, S.; Panay, N.
Abstract: Premature ovarian insufficiency (POI) refers to the loss of ovarian activity before the age of 40 years, which leads to hypoestrogenism and amenorrhea. The diagnosis of POI in a young woman has potentially life-changing physical and emotional consequences for both the patient and her family. Therefore, it is very important that the diagnosis is correct and that it is made in a timely manner. Unfortunately, the diagnosis and therefore the effective treatment of POI are often delayed, which underlines the need for education of the broad medical community on the issue. A panel of menopause experts reviewed and critically appraised the literature, and present: (1) the diagnostic approach to POI, (2) the investigation of the etiology of this condition, (3) the therapeutic strategy regarding both hormone replacement therapy and fertility, and (4) the long-term follow-up and management for ensuring quality of life, as well as urogenital, cardiovascular, bone and mental health. The ultimate goal of this article is to provide a complete toolkit for the primary care physician to have easy access to all the information needed for the optimal management of women with POI, in the context of evidence-based and personalized medicine. HIGHLIGHTS: Premature ovarian insufficiency occurs in 1% of the female population of reproductive age, yet the diagnosis is often delayed, with severe physical and emotional consequences for the patient. Primary care physicians should be aware of the possibility of premature ovarian insufficiency in young women presenting with menstrual irregularity. Prompt initiation of hormone replacement therapy ensures quality of life and prevents osteoporosis and cardiovascular disease. Women seeking fertility should be referred to specialists to discuss assisted reproduction options.